Impact of cerebral aneurysm size on distal intracranial hemodynamics and changes following flow diversion. Issue 3 (June 2022) - Brunozzi, Denise; See, Alfred; Rizko, Mark; Choi, Jason; Atwal, Gursant; Alaraj, Ali
Background: The impact of cerebral aneurysm size on distal intracranial hemodynamics such as arterial pressure and Pulsatility Index is not completely understood, either before or after flow diversion. Objective: The aim of the study is to assess the impact of aneurysm size on distal Pulsatility Index and pressure before and after flow diversion. Methods: From December 2015, prospective measurement of middle cerebral artery pressure and Pulsatility Index was performed in consecutive patients with unruptured cerebral aneurysms in the cavernous to communicating segments of the internal carotid artery, which were treated with single flow diversion. Pressure and Pulsatility Index were recorded at the M1-segment ipsilateral to the cerebral aneurysm. Ratio of middle cerebral artery to radial arterial pressure (pressure ratio) was calculated to control for variations in systemic blood pressure. Correlations between aneurysm size and pressure ratio and Pulsatility Index were assessed before and after treatment. Results: A total of 28 aneurysms were treated. The mean aneurysm size was 7.2 mm. Aneurysm size correlated linearly with systolic pressure ratio (1% pressure ratio increase per mm aneurysm size increase, P = 0.002, r 2 = 0.33), mean pressure ratio (0.6% per mm, P = 0.03, r 2 = 0.17) and Pulsatility Index (5% Pulsatility Index increase per mm, P = 0.003, r 2 = 0.43). After flow diversion, aneurysm size preserved a linear correlation with the systolic pressure ratio (1% per mm, P = 0.004, r 2 = 0.28), but not with the mean pressure ratio (0.4% per mm, P = 0.15, r 2 < 0.1) or Pulsatility Index (0.3% per mm, P = 0.78, r 2 < 0.1). Conclusion: Aneurysm size affects distal hemodynamics: patients with larger aneurysms have increased systolic and mean pressure ratio, and increased Pulsatility Index. After flow diversion, mean pressure ratio and Pulsatility Index no longer associate with the aneurysm size, suggesting an effect of the flow diversion also on distal intracranial hemodynamics.